БІЛІМ БЕРУДЕГІ ИННОВАЦИЯЛЫҚ ҮДЕРІСТЕР - Шолпанбаева, Г.А.; Феклюнина, А.А. (My University, 2019)
Аннотация В статье рассмотрен вопрос об инновациях в современных образовательных учреж- дениях, возможности и значение творческого их применения в массовом опыте, критерии пе- дагогических инноваций и результативности таких нововведений. Целью является качествен- ное изменение личности учащегося по сравнению с традиционной системой. Аbstract The article deals with the issue of innovations in modern educational institutions, the possibi- lities and importance of their creative application in the mass experience, the criteria of pedagogical innovations and the effectiveness of such innovations. The aim is a qualitative change in the perso- nality of the student in comparison with the traditional system.
Innovative processes in education
Keywords: инновация; прогресс; информационно-коммуникативные технологии; innovation; progress; information and communication technologies